NON-MINERAL INORGANIC CONSTITUENTS OF BUKIT ASAM COAL NATURE AND MODE OF OCCURRENCE - Susilawati, Rita (Buletin Sumber Daya Geologi, 2015)
The nature and mode of occurrence of the non-mineral inorganic fractions in coal from the Bukit Asam coalfield South Sumatra Basin Indonesia were analysed using a combination of selective leaching, low temperature ashing, XRD, XRF and electron micropobe techniques. Geologically the rank of coal at Bukit Asam was influenced by igneous intrusion. Fourteen coal samples were used in this study. Samples are chosen to represent different rank levels as well as seam horizons. The inorganic elements, in the form of dissolved salts, exchangeable ions and organometallic complexes, although present in small proportions, contribute significantly to the mineral matter components of Bukit Asam low rank coal. Electron microprobe analysis showed small but significant concentrations of inorganic elements (Al, Ca and Fe) occurring in the individual macerals in two sub bituminous and twosemi anthracite samples. There is a tendency for some of the elements, particularly Ca and Al to be lost from the organic matter with rank advance. The concentrations of elements indicated by the microprobe are relatively in good agreement with the levels of element mobility indicated by selective leaching of the same whole-coal samples. The results of this study also suggest that non-mineral inorganic was likely act as a precursor for the reactions resulting in the formation of new minerals in the high rank coals at Bukit Asam.